(untitled) - Lesk, Micheal (Boston, 2004)
Useful for digital library projects in all kinds of settings, including commercial and community ventures, meseums, research institutions, and schools. Covers the entire spectrum of media, including text, all kinds of images, audio, and video. Provides practical advice on achieving the best of what is possible while avoiding common pitfalls. Filled with case studies and references to valuable outside resource
Keywords: Libraries,Digital libraries; Special collections,Computer files; United States; United States